Elektronik ticaret - Algül, Ercan (My University, 2003)
Bu tezin birinci bölümünde temel kavramlar üzerinde durulmuştur; Yeni ekonomi, internet, intranet, extranet, e-ticaret, mobil e-ticaret gibi kavramlar açıklanmıştır. Tezin ikinci bölümünde ise e-ticaret, tanımı ve önemi, kapsamı, tarihsel gelişimi, yararları, e- ticarette karşılaşılan sorunlar; e-ticaret yöntemleri; e- ticaret stratejisi; e-paranın analizi, hız, oyuncular, sorumluluklar üzerinde durulmuştur. Tezin üçüncü bölümünde e- ticarette ödeme yöntemleri; SET protokolü ve kredi kartları, akıllı kartlar, e-para, e-paranın avantajları dezavantajları üzerinde durulmuştur. Tezin dördüncü bölümünde e- ticaretin sosyal, hukuki ve vergi boyutu üzerinde durulmuş ve Türkiye'de şu anda yürürlükte olan kanun maddeleriyle e-ticaretten doğan hukuki sorunların giderilemediği ifade edilmiştir. Beşinci bölümde web sitesinin kurulması, yayınlanması ve tanıtımı konuları ele alınmıştır.

In the First section of this thesis is dwelt on basic concepts such as ; new economy, internet, intranet, extranet, e-commerce, mobile e-commerce were explained. In the second section of the thesis is dwelt on those subjects; the definition, the importance, the extension, the historical development, the benefits, confrontation problems; the methods of e-commerce, the strategy of e-commerce; the analysis of e-money, speed, players, responsibilities of the e- commerce. In the third section of the thesis is dwelt on those subjects; the methods of payment of the e-commerce, the protocol of the SET and credit cards, intelligent cards, e-money, the advantages of e-money, the disadvantages of the e-money In the fourth section of the thesis is dwelt on those subjects; the social, legal and taxable dimensions of the e-commerce and it was explained that laws now are was in force in Turkey aren't sufficient to solve the legal problems of e- commerce. In the fifth section of the thesis is dwelt on those subjects; the foundation of a web site, the publication of a web site and the introduction of it.
Keywords: Elektronik ticaret; Ticaret